Ռազմական օմբուդսմենի ինստիտուտը` որպես Զինված ուժերի մարտունակության գրավական (կամ ինչո՞ւ է անհրաժեշտ ռազմական օմբուդսմենի ինստիտուտի ստեղծումը) - Նորիկ Նորիկյան (ՀՀ ԳԱԱ հրատ.)
В статье представлен вопрос о необходимости внедрения института военного омбудсмена как отдельного, гражданского, независимого института, учитывая, что он является одним из ключевых факторов, определяющих боеспособность вооружённых сил. The article highlights the need for introduction of the institute of military ombudsman and its peculiarities as a separate and independent civil institute, considering it as one of the most important guarantees of armed forces efficiency.
Keywords: Law; Military Science